Remission of migraine after clipping of saccular intracranial aneurysms. (7th October 2014) - Lebedeva, E. R.; Busygina, A. V.; Kolotvinov, V. S.; Sakovich, V. P.; Olesen, J.
<x xml:space="preserve">Abstract</x> Background Unruptured saccular intracranial aneurysm (SIA) is associated with an increased prevalence of migraine, but it is unclear whether this is altered by clipping of the aneurysm. The aim of our study was to determine whether remission rate of migraine and other recurrent headaches was greater in patients with SIA after clipping than in controls. Methods We prospectively studied 87 SIA patients with migraine or other recurrent headaches. They were interviewed about headaches in the preceding year before and 1 year after clipping using a validated semi‐structured neurologist conducted interview. The remission rates of migraine and tension‐type headache (TTH) in these patients were compared to 92 patients from a headache center. Diagnoses were made according to the ICHD‐2. Results During 1 year preceding rupture 51 patients with SIA had migraine. During the year after clipping, this was reduced by 74.5% (P < 0.0001). At first encounter, 47 control patients had migraine during the preceding year, and during 1 year of treatment, it was 41, a reduction 12.8% (P > 0.5). The decrease of migraine in SIA patients was significantly higher than in controls: 74.5% vs 12.8% (P < 0.001). A history of TTH was given by 33 patients with SIA during the year preceding rupture and by 44 during 1 year after clipping (P > 0.75). Forty‐one control patients had TTH, 27 after 1 year of treatment, a reduction 34.1% (P < 0.05). No factors except clipping of the aneurysm could explain the remission of migraine. Conclusions Migraine prevalence in patients with SIA decreases significantly after clipping. Further comparative studies of migraine after coiling vs clipping in SIA patients are needed.